Small and Medium Enterprises: Asymmetric Information and Critical Factors Affecting Bank Financing - Marimuthu, Maran (2015)
Small and Medium Enterprises (SMEs) are backbone of both developed and developing economies. They form substantial number of total businesses, contribute to Gross Domestic Production (GDP) and employment. In spite of the significant role played by SMEs in economic development and growth this sector of economy faces problems in the business start-up, growth and survival. The most critical problem they face is access to finance from financial institutions. SMEs argue that supply of finance is not made available to them; whereas financial institutions say loans for SMEs remain on the lower side due to demands being unqualified i.e., loan applications are not meeting the requisite criteria. This research will focus SMEs on both their supply and demand side perspectives. This paper explains the criteria set by financial institutions and there will be cross referral from the demand side perspective. The central concern of this concept paper is to capture the types of asymmetric information that exists between the borrowers and suppliers of funds and eventually to model the financial fundamentals and non-financial aspects that affect loan approval. This study will help SMEs to be better prepared so as to meet lenders’ requirements for ultimate fulfillment of their financing needs through borrowing.